The Restoration of the Monarchy: A Topic of the Romanian Presidential Elections of 1990, 1992, and 1996 - MUREȘAN, Marius (Studia Universitatis Babeș-Bolyai Historia, 2025)
Following the anti-communist revolution in Romania in December 1989, the newly-established government was preoccupied with facilitating an expeditious institutional transition and securing public legitimacy. Consequently, the inaugural elections were scheduled to take place within a mere six months following the collapse of the communist regime. The 1990 election campaign included debates about the economic model that the country should adopt, the orientation of foreign policy, and so forth. However, it also encompassed related themes, which were proposed mainly by the neo-communist power. These included the possibility of restoring the monarchy, the intention of the historical parties to return to the interwar model of society, the restitution of land to former landowners, and revenge against the several million Romanians who had been members of the communist party. A particularly noteworthy topic, including from a symbolic perspective, was the status of the former King Michael I. This study aims to analyse the manner in which this campaign theme was utilised in the 1990, 1992, and 1996 elections, the objective for which it was advanced, the defensive and responsive mechanisms employed, and the extent to which it influenced the outcome of the vote. In order to reach a conclusion, this study draws on the research of historians and political analysts, as well as newspapers from the period in question. Rezumat: După Revoluția anticomunistă care a avut loc în România în decembrie 1989, noua putere a fost preocupată de realizarea unei tranziții cât mai rapide din punct de vedere instituțional, astfel că primele alegeri au fost programate la mai puțin de șase luni de la căderea regimului comunist. Campania electorală din 1990 a inclus dezbateri despre modelul economic pe care țara trebuia să îl adopte, despre orientarea politicii externe etc., dar și teme conexe, propuse mai ales de puterea neocomunistă, precum posibilitatea restaurării monarhiei, intenția partidelor istorice de a reveni la modelul societății interbelice, retrocedarea pământurilor către foștii moșieri, răzbunarea împotriva celor câteva milioane de români care au fost membri ai Partidului Comunist. Un subiect care s-a evidențiat, inclusiv la nivel simbolic, a fost cel referitor la statutul fostului rege Mihai I, iar cercetarea de față își propune să analizeze modul în care această temă de campanie a fost utilizată în cadrul alegerilor din 1990, 1992 și 1996, scopul pentru care a fost promovată, care au fost mecanismele de apărare sau de răspuns, respectiv în ce mod a influențat rezultatul votului. Pentru a ajunge la o concluzie, vom face apel la cercetările unor istorici și analiști politici, precum și la ziarele perioadei. Cuvinte-cheie: monarhie, republică, alegeri, post-comunism, politică